Soluções para a tarefa
Respondido por
1
x⁴+2x³+4x-3 | P(x)
x²+2x-1
R(x) = 2x-2
Então:
x⁴+2x³+4x-3 = P(x)·(x²+2x-1)+(2x-2)
P(x)·(x²+2x-1) = x⁴+2x³+4x-3-(2x-2)
P(x)·(x²+2x-1) = x⁴+2x³+4x-3-2x+2
P(x)·(x²+2x-1) = x⁴+2x³+2x-1
P(x) = x⁴+2x³+2x-1
x²+2x-1
Realizando a divisão pelo método da chave:
x⁴+2x³+2x-1 |x²+2x-1
-x⁴-2x³+x² x²+1
\ \ x²+2x-1
-x²+2x-1
\
Alternativa B.
x²+2x-1
R(x) = 2x-2
Então:
x⁴+2x³+4x-3 = P(x)·(x²+2x-1)+(2x-2)
P(x)·(x²+2x-1) = x⁴+2x³+4x-3-(2x-2)
P(x)·(x²+2x-1) = x⁴+2x³+4x-3-2x+2
P(x)·(x²+2x-1) = x⁴+2x³+2x-1
P(x) = x⁴+2x³+2x-1
x²+2x-1
Realizando a divisão pelo método da chave:
x⁴+2x³+2x-1 |x²+2x-1
-x⁴-2x³+x² x²+1
\ \ x²+2x-1
-x²+2x-1
\
Alternativa B.
Perguntas interessantes
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás